Cleaning Zirconia Surface Prior To Bonding: A Comparative Study of Different Methods and Solutions. Issue 3 (1st June 2021) - Sulaiman, Taiseer A.; Altak, Ali; Abdulmajeed, Awab; Rodgers, Brandon; Lawson, Nathaniel
Abstract: Purpose: To evaluate resin cement bond strength after removal of salivary contamination from a zirconia surface using different cleaning solutions and air‐borne particle abrasion. Materials and methods: One‐hundred and twenty zirconia specimens (KATANA STML, Noritake) were prepared and divided into 12 groups (n = 10). Groups were subjected to a notched‐edge shear bond strength test (ISO 29022) to analyze the bonding efficiency of a resin cement (Panavia V5, Kuraray Noritake Dental Inc.) before and after contamination with saliva. Group 1 (control) was prepared and cemented without salivary contamination. Group 2 was coated with ceramic primer (Clearfil Ceramic Primer Plus, Kuraray Noritake Dental Inc.) then subjected to salivary contamination then tested. Group 3 was contaminated, cleaned by air‐borne particle abrasion, ceramic primer and resin cement applied, and tested. Groups 4 to 12 were contaminated, and then different cleaning solutions (water, 4.5% hydrofluoric acid, 35% phosphoric acid, Ivoclean, KATANA cleaner, Zirclean, sodium hypochlorite 4%, and 7.5%) were used to decontaminate the zirconia surface, followed by ceramic primer, resin cement application, and tested. One‐way ANOVA and Tukey post‐hoc analysis was used to analyze the data. Results: One‐way ANOVA showed statistical differences among cleaning procedures ( p < 0.001, F = 13.48). Air‐borne particle abrasion was the only group which provided a bond strength (21 ± 2.8 MPa) that was not statistically different than the control group in which no contamination occurred (25.3 ± 3.3 MPa) ( p = 0.247). The use of hydrofluoric acid and zirconia cleaning solutions resulted in bond strengths values which were not statistically different from each other (17.5‐19.1 MPa). Conclusion: Air‐borne particle, zirconia cleaning solutions and hydrofluoric acid are feasible to decontaminate the zirconia surface from saliva prior to bonding the restoration.